Drinking policies and exercise-associated hyponatraemia: is anyone still promoting overdrinking?. Issue 10 (9th April 2008) - Beltrami, F G; Hew-Butler, T; Noakes, T D
Abstract : Objectives: The purpose of this review is to describe the evolution of hydration research and advice on drinking during exercise from published scientific papers, books and non-scientific material (advertisements and magazine contents) and detail how erroneous advice is likely propagated throughout the global sports medicine community. Design: Hydration advice from sports-linked entities, the scientific community, exercise physiology textbooks and non-scientific sources was analysed historically and compared with the most recent scientific evidence. Conclusions: Drinking policies during exercise have changed substantially throughout history. Since the mid-1990s, however, there has been an increase in the promotion of overdrinking by athletes. While the scientific community is slowly moving away from "blanket" hydration advice in which one form of advice fits all and towards more modest, individualised, hydration guidelines in which thirst is recognised as the best physiological indicator of each subject's fluid needs during exercise, marketing departments of the global sports drink industry continue to promote overdrinking.